TEleRehabilitation foR Aphasia (TERRA) phase II trial design - Christy Cassarly; Alexandra Basilakos; Lisa Johnson; Janina Wilmskoetter; Jordan Elm; Argye E. Hillis; Leonardo Bonilha; Chris Rorden; Gregory Hickok; Dirk-Bart den Ouden; Julius Fridriksson (Contemporary Clinical Trials Communications)
Background and purpose: Despite comprehensive evidence that supports the utility of aphasia therapy in persons with chronic (≥6 months) stroke-induced aphasia, the amount of therapy provided to patients in the United States is typically far less than what is likely necessary to maximize recovery. Two potential contributors to this discrepancy are limited access to rehabilitation services due to the availability of providers and logistical difficulties with transportation. One way to increase access to aphasia therapy is to rely on telerehabilitation. Methods: The TEleRehabilitation foR Aphasia (TERRA) trial is a prospective, randomized, rater-blinded, multicenter phase II non-inferiority trial to evaluate telerehabilitation for aphasia therapy in persons with chronic post-stroke aphasia. Participants are randomized (1:1) to receive either aphasia remote therapy or in-clinic therapy for 30 total days of treatment (15 days of a semantically focused approach and 15 days of a phonologically focused approach) for 45 min per day. A total of 100 adults (ages 21–80) with a history of left hemisphere ischemic or hemorrhagic stroke incurred at least 12 months prior to study enrollment will be randomized. The trial will be conducted at the clinical research facilities at two sites: the Medical University of South Carolina and the University of South Carolina. Conclusions: This paper details the design of the TERRA trial, which aims to test whether aphasia therapy delivered by a remote speech-language pathologist through videoconferencing (i.e., via telerehabilitation) is not clinically worse than in-clinic therapy for individuals with chronic post-stroke aphasia to provide an opportunity to move to a definitive phase III trial.